Outcome of ACL reconstruction : a comparison between biotransfix screw and all-inside technique - Nik Alyani Nik Abdul Adel (Kulliyyah of Medicine, International Islamic University Malaysia, 2017)
This is a cross sectional study of 40 patients with Anterior Cruciate Ligament (ACL) injury treated with ACL reconstruction surgery in Hospital Sultanah Nur Zahirah, Kuala Terengganu and Hospital Kemaman, Kemaman, Terengganu. The aim of this study is to compare outcomes of patient after an ACL reconstruction between two techniques: biotransfix screw or all inside technique. 20 patients in each group of technique were selected and agreed to participate in this study. They were evaluated for the functional outcome with IKDC score, quality of life SF-36 questionnaire and time taken to return to normal activities at 18-24 months post-operative. There were 32 patients from HSNZ and another 8 from Hospital Kemaman. 37 patients were male and all of them were Malay. Mean age was 25.03 years old, range from 17 to 41 years old. 25 of them were working as office worker and the rest were a field worker. 37.5% were smoker at the time of surgery, while another 62.5% were nonsmoker. Right knee involved in 27 patients. Patients in biotransfix screw operated at mean of 21.3 months after the injury while in all inside technique was at mean of 17.65 months. Mean BMI was 24.58 with 42.5% of them were normal, 40% were overweight, 10% were underweight and 7.5% were obese. The biotransfix screw technique scored slightly better in all categories except for physical function, body pain and role emotional in SF 36 questionnaires compare to all inside technique but they were not statistically significant. Both groups have mean IKDC score of 82.99. Time taken to return to normal activity level was at mean of 46.3 weeks which was about similar in both groups. Re rupture rate were 10% in biotransfix screw technique and 5% in all inside technique. None of them has any form of infection. There were also no correlation in between outcome with age, tobacco use, BMI, duration of injury until operation and occupation of the patient in both techniques. As a conclusion, the functional outcome, quality of life and time return to normal activity were not statistically has a significant difference between biotransfix screw and all inside technique. There were also no correlations between factors study with outcome in both groups.